Planning Planning Terra dei fuochi: Soluzioni Rigenerative per Territori Malleabili - Guida, Giuseppe; Bocchino, Chiara (Contesti. Città, territori, progetti, 2026)
The worsening of climatic, environmental and socio-economic crises highlights the urgent need to develop innovative approaches for territorial governance, promoting public policies and urban planning strategies capable of responding to the direct and indirect threats associated with these phenomena. Territories are exposed not only to declared risks but also to latent risks, characterized by dynamic evolution and not always evident. Managing such challenges requires a kind of planning which embraces a paradigm of radical transformation and adaptation. The concept of ‘territorial malleability’ proves particularly fertile in this context. This contribution aims to explore the implications of such theories, in particular in the territory between Marcianise and Caivano. This fragment of territory has been the subject of design experiments carried out within the Urban Planning Laboratory at the Department of Architecture and Industrial Design at the University of Campania L. Vanvitelli.